Legal Analysis of the Criminal Policy on Incest in Indonesia According to Law No. 1 of 2023 - Yusar, Muhamad; Rasmah, Rasmah (LPPM Universitas Primagraha, 2023)
Setting the crime of incest is in Article 46 of Act No. 23/2004 on the Elimination of Domestic Violence and Article 81, paragraph (1) of Act No. 23/2002 on Child Protection. However, the setting does not include the crime of incest committed by the parents of the child. In order to reform the criminal law, a new formulation of the article should be added to encompass parents who commit the crime of incest against their son. This should be done by weighing the criminal sanctions (existing criminal penalties plus one-third).